Analysis of Competencies, Individual Behavior and Trainee Satisfaction in Human Reseource Development Center Regional Bukittinggi - Yuniara Simanjorang; Aldri Frinaldi (Program Pascasarjana Universitas Negeri Makassar, 2022)
This study aims to analyze the competence ofparticipants in theera of the covid-19 pandemic at the Bukittinggi Regional Human Resources Development Center (PPSDM Pusat Pengembangan Sumber Daya Manusia Regional Bukittinggi), analyze the individual behavior of trainees in the era of the covid-19 pandemic at the Bukittinggi Regional PPSDM, analyze the satisfaction of trainees in the era of the covid-19 pandemic at the Bukittinggi Regional PPSDM. This type of research is quantitative with descriptive methods and is carried out at the Bukittinggi Regional PPSDM. The data collection technique spread the questionnaire with a population of 120 trainees and validation tests using softwere Statistical Product and Service Solution (SPSS) version 24. The results of this study illustrate 1) Kompetension got the highest mean score of 4.675 and TCR of 93.5% is already very good. 2) Individual behavior, getting the highest mean value of 4.325 and TCR of 86.5% is good. 3) The e-learning method is a statement with the lowest value, namely with a mean value of 3.26 and TCR of 65.167% knowledge which is still low. 4) Customer satisfaction is a statement with the lowest value, namely with a mean value of 3.26 and TCR of 65.167% knowledge which is still low. 4) Customer satisfaction is a statement with the lowest value of 3.26 and TCR of 65.167% knowledge which is still low. 4) Customer satisfaction is a statement with the lowest value of 3.26 and TCR of 65.167% knowledge which is still low. got the highest score of the mean of 4.65 and the TCR of 93% with a good category. It can be concluded that of the 4 variables, 3 of them with a high category are good while the low category is in the knowledge variable of e-learning learning methods.